Adolescents' personal conceptions of intelligence: the development of a new scale and some exploratory evidence - Luísa Faria (1997)
This study presents the building of an instrument to measure personal conceptions of intelligence based upon Dweck research, and some exploratory evidence. The instrument is directed to adolescents, has got more items than the original one and incorporates new aspects, such as the importance of effort and ability in relation with personal conceptions of intelligence. The results of a factor analysis evidenced the existence of two distinct factors - a static and a dynamic one - that explain together 31.7% of the total variance. The internal consistency of the scales evidenced alpha coefficients between .74 and .80. The results of a test-retest reliability study (with a month interval) proved to be better for the static scale than to the the dynamic one, as well as the results of an external validity study (correlations with grade point average). Some differential exploratory studies showed differences in personal conceptions of intelligence related to school grades (5th to 11h): the scores increased from the 5th to the 11th grade, showing that older students were less ''static'' (more ''dynamic''), and also related to the socio-economic status (high vs. low): the higher SES subjects appeared less ''static'' (more ''dynamic'') than the lower SES subjects.